Regioselectivity of the glycosylation of N-dimethylmaleoyl-protected hexosamine acceptors. An experimental and DFT approach - Colombo, María Inés (2011)
Both anomers of the methyl glycoside of 6-O-benzyl-N-dimethylmaleoyl-D-allosamine (6 and 7) are glycosylated exclusively on O3 when reacting with the trichloroacetimidate of peracetylated α-D-galactopyranose (5). This regioselectivity is expected for 6, the α-anomer, as a strong hydrogen bond of its H(O)3 with the carbonyl group of the dimethylmaleoyl group occurs, as shown by NMR temperature dependence. However, this hydrogen bond was not encountered experimentally for 7, the β-anomer. A DFT study of the energies implied in an analog of the glycosylation reaction charged intermediate has explained neatly this behavior, in terms of strong hydrogen bonds occurring at these charged intermediates. This approach explains both the experimental regioselectivities found for 6 and 7, but furthermore the calculations have shown a marked agreement with the regioselectivities found for other related compounds in the literature.